Case Report: The Effect of Neurofeedback Therapy on Reducing Symptoms Associated with Attention Deficit Hyperactivity Disorder: A Case Series Study - Mostafa Deilami; Asghar Jahandideh; Yousef Kazemnejad; Yousef Fakour; Shiva Alipoor; Fatemeh Rabiee; Ghazal Saadat Pournesaie; Rosemarie Noot Heidari; Seyed Aliasghar Mosavi (Basic and Clinical Neuroscience, 2016)
Introduction: This study aimed to evaluate the effectiveness of neurofeedback on attention deficit hyperactivity disorder. Methods: This is a quasi-experimental study without a control group. The study population included all children aged 5 to 12 years old affected with attention deficit hyperactivity disorders in Tehran, Iran who were referred to psychiatric clinics and given the diagnosis. The sample included 12 children with attention deficit hyperactivity disorder who were selected based on their availability (non-random sampling). They received 30 sessions of neurofeedback treatment, 2 times per week. Before and after neurofeedback training, the children were evaluated and compared with the use of cognitive assessment system test. Data were analyzed using dependent T-test. Results: The total mean score for pretest was 88.81 while the total mean score for the post test was 82.23. The mean in pretest for attention hyperactivity disorder was higher than the mean in the post test. Moreover, The difference of pretest and post test scores of children affected with learning disorder associated with ADHD was calculated that showed significant (P=0.003). Conclusion: Neurofeedback is effective in the improvement of attention deficit hyperactivity disorder.